Influence of hydrodynamics on the larval supply to hydrothermal vents on the East Pacific Rise - Adams, D K (Massachusetts Institute of Technology and Woods Hole Oceanographic Institution, 2007)
Examination of the scales at which larval supply varies spatially and temporally, and correlation with concurrent physical observations can provide insights into larval transport mechanisms that contribute to structuring marine benthic communities. In order to facilitate field studies, this thesis first provides new morphological and genetic identifications for hydrothermal vent gastropod larvae along the northern East Pacific Rise. Daily and weekly variability in the supply of hydrothermal vent gastropod larvae to two hydrothermal vents, 1.6 km apart on the East Pacific Rise, were quantified concurrently with current velocity observations. The magnitude and temporal pattern of larval supply differed between vent sites, despite their close proximity. A strong correlation between along-axis flow and daily larval supply suggested that larval supply occurred primarily via along-axis transport between local sources 1-2 km apart. However, weekly larval supply appeared to be driven by larger spatial scales through losses associated with cross-axis flows and the passage of mesoscale eddies. Tracer movement within a quasi-geostrophic eddy model was consistent with the observations of decreased larval supply concurrent with an eddy observed via satellite altimetry. The tracer movement also indicated that deep eddy-induced flow could facilitate a long-distance dispersal event, enhancing dispersal between vents 100s km apart.
Keywords: HOV Alvin (Human Occupied Vehicle)